2023
DOI: 10.1182/bloodadvances.2022008272
|View full text |Cite
|
Sign up to set email alerts
|

Engineering amino acid uptake or catabolism promotes CAR T-cell adaption to the tumor environment

Abstract: Cancer cells take up amino acids from the extracellular space to drive cell proliferation and viability. Similar mechanisms are employed by immune cells. The result is competition between conventional T cells, or indeed CAR-T cells, and tumour cells for limited availability of amino acids within the environment. We demonstrate that T cells can be re-engineered to express SLC7A5 or SLC7A11 transmembrane amino acid transporters alongside chimeric antigen receptors (CAR). Transporter modifications increase CAR-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Overexpression of the amino acid transporters SLC7A5 or SLC7A11 in CAR-T cells can enhance arginase amino acid uptake and boost T cell proliferation and anti-tumor activity. [151] Moreover, elevated PGC-1α expression in CD8 + T cells can increase mitochondrial biogenesis and tness, consequently inhibiting the exhaustion progression of TILs. [4,69] Additionally, tumor-speci c CD8 + T cells can also be metabolically reprogrammed to enhance effector functions by increasing phosphoenolpyruvate production through the overexpression of PCK1.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Overexpression of the amino acid transporters SLC7A5 or SLC7A11 in CAR-T cells can enhance arginase amino acid uptake and boost T cell proliferation and anti-tumor activity. [151] Moreover, elevated PGC-1α expression in CD8 + T cells can increase mitochondrial biogenesis and tness, consequently inhibiting the exhaustion progression of TILs. [4,69] Additionally, tumor-speci c CD8 + T cells can also be metabolically reprogrammed to enhance effector functions by increasing phosphoenolpyruvate production through the overexpression of PCK1.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…So the proliferation and activation of T cells are hindered, especially effector T cells. Besides, the lack of tryptophan or cysteine inhibits the proliferation of T cells and affects the role of T cells ( 75 ). Moreover, CD8+T cells lose the expression of the mechanistic target of rapamycin (mTOR) due to the deficiency of RagD-dependent amino acids in TME.…”
Section: Effect Of Metabolism On Immune Cellsmentioning
confidence: 99%
“…The growth of multiple T cells is connected with the amount of amino acids. Promoting the inflow of amino acids is conducive to the growth of T cells and eventually affects the anti-tumor immune response ( 75 ). Besides, it is indicated that the function of effector T cells can be improved by supplementing amino acids, and anti-tumor immunity can be enhanced when anti-PD-L1 antibody therapy is performed at the same time ( 5 ).…”
Section: Targeting Metabolism To Explore and Promote Tumor Immunotherapymentioning
confidence: 99%
“…To overcome arginine depletion, Mussai, De Santo and colleagues ectopically expressed enzymes involved in either arginine catabolism (ARG1/ARG2) or arginine resynthesis [arginosuccinate synthase (ASS) and ornithine transcarbamylase (OTC)] in CD33‐ as well as GD2‐targeted CAR T cells. They found that these modified CAR T cells exhibited enhanced in vivo anti‐tumor responses against human AML and neuroblastoma [ 213 , 214 ]. Similarly, our group and others have modulated the expression of glucose, glutamine, and arginine transporters, among others, in order to enhance CAR T cell function in nutrient‐deprived tumor microenvironments (Fig.…”
Section: Metabolic Interventions To Optimize Adoptive T Cell Immunoth...mentioning
confidence: 99%